THE THE EFFICACY OF BACTERIAL AND FUNGAL ANTAGONIST SUSPENSIONS IN CONTROLLING FOLIAR MILDEW DISEASE IN ZUCCHINI PLANTS: - - Yan Ramona; Martin A. Line; I Gusti Ayu Agung Septiari; Ida Bagus Gede Darmayasa; I Dewa Agung Panji Dwipayana; Kalidas Shetty (BIOTROPIA, 2025)
ARTICLE HIGLIGHTS- Diverse microbial antagonists can be used as alternatives to control foliar disease - Microbial agents offer zucchini protection against downy mildew causing microbes- Biocontrol agents effectively control mildew infection in zucchini plants- Diverse microbial antagonists have potential to control foliar disease in zucchini - New bio-based strategy supports sustainable crop disease management- Diverse microbial antagonists are promising for controlling mildew in zucchiniABSTRACTDowny mildew is recognized as a major constraint in zucchini production, caused by obligate fungal-like pathogens that thrive under humid conditions. In this study, the efficacy of selected bacterial (Lysobacter antibioticus Bali G, Pseudomonas corrugata SAJ6) and fungal (Trichoderma sp. Td22) antagonists was evaluated for the management of this foliar disease on zucchini plants as an alternative to chemical fungicides. The efficacy of these bacterial and fungal antagonists against a suspected downy mildew pathogen was assessed on zucchini leaves in a glasshouse. It was found that the antagonists provided 22 - 83% protection (P < 0.05) against the pathogen two weeks after application. However, the level of protection declined over time, with 46 - 60% of leaves infected five weeks after pathogen exposure, regardless of treatment. The combination of Trichoderma sp. Td22, the most effective agent, with either Lysobacter antibioticus Bali G, Pseudomonas corrugata SAJ6, or both, was observed to reduce its overall effectiveness. Survival of the biological agents on leaf surfaces was low, although prior research has indicated that survival may not be essential for sustained disease control. Further investigation is required to determine the potential role of these agents in inducing systemic acquired resistance in crops such as grapes and poppies. For commercial application, repeated treatments may be necessary to maintain disease management. Notably, the protection provided by Trichoderma sp. Td22 was found to be comparable to that of chemical treatments, representing a promising step toward more sustainable agricultural practices.